Pengaruh Massa Dan Waktu Kontak Adsorben Cangkang Buah Ketapang Terhadap Efisiensi Penyisihan Logam Fe Dan Zat Organik Pada Air Gambut - Isra Desmita Putri; Syarfi Daud; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Adsorption is the binding process of a molecule from the gas or liquid phase into an adsorbent from an adsorbate. Adsorption is one method of processing peat water. Tropical Almond shell is one of the organic wastes that has the potential to be used as an adsorbent because it contains cellulose, hemicellulose and lignin. The purpose of this study was to determine removal efficiency of Fe and organic matter in the peat water, calculating the adsorption capacity and determine thw appropriate type of isotherm. Variable that was given in this research consisted by mass variation 4,5 dan 6 gr and contact time of 30, 60 and 90 minutes.the resultsof the study showed the efficiency of removal of Fe and organic matter concentrations higher 53,62% and 41,39% by mass of adsorbent 6 gr with a contact time 60 minutes. Mettal adsorption capacity of Fe achieved the highest on the mass of 6 grams with a contact time of 60 minutes amounted to 0,00754 mg Fe/gr, while the adsorption capacity of organic matter achieved the highest on the mass of 4 grams with a contact time of 60 minutes as amounted to 10,125 mg organic matter/gr. Types of adsorption isotherms corresponding to Fe and organic matter by Tropical Almond Shell (Terminalia Cattapa) adsorbents is Freundlich isotherm with R2 values of 0,951 to 0,9936 for Fe and organic matter.Keyword : Adsorption, Tropical Almond shell Adsorbent, Peat Water.